2017
DOI: 10.1111/cns.12710
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA and its contribution to autism spectrum disorders

Abstract: Recent studies have indicated that long noncoding RNAs (lncRNAs) play important roles in multiple processes, such as epigenetic regulation, gene expression regulation, development, nutrition-related and other diseases, toxic response, and response to drugs. Although the functional roles and mechanisms of several lncRNAs have been discovered, a better understanding of the vast majority of lncRNAs remains elusive. To understand the functional roles and mechanisms of lncRNAs is critical because these transcripts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 152 publications
(245 reference statements)
1
41
0
Order By: Relevance
“…In addition, results from flow cytometry assay demonstrated that MEG3 over-expression enhanced the chemo-sensitivity of BC cells to DDP treatment ( Figure 3C). Moreover, results of western blot analysis revealed that DDP treatment further up-regulated the protein levels of cleaved caspase-3 and LncRNAs has been extensively researched in a variety of pathophysiological processes, including autism spectrum disorders [21], cancers [22], cardiovascular disease [23], Alzheimer's disease [24] and in reproduction and development [25]. Because prior findings revealed low expression of MEG3 in BC tissues [19], we conducted in vitro experiments using T24 and 5637 cells to investigate the role of MEG3 in the metastasis and chemotherapy sensitivity of BC cells.…”
Section: Effects Of Meg3 Over-expression On Bc Cell Migration and Invmentioning
confidence: 99%
“…In addition, results from flow cytometry assay demonstrated that MEG3 over-expression enhanced the chemo-sensitivity of BC cells to DDP treatment ( Figure 3C). Moreover, results of western blot analysis revealed that DDP treatment further up-regulated the protein levels of cleaved caspase-3 and LncRNAs has been extensively researched in a variety of pathophysiological processes, including autism spectrum disorders [21], cancers [22], cardiovascular disease [23], Alzheimer's disease [24] and in reproduction and development [25]. Because prior findings revealed low expression of MEG3 in BC tissues [19], we conducted in vitro experiments using T24 and 5637 cells to investigate the role of MEG3 in the metastasis and chemotherapy sensitivity of BC cells.…”
Section: Effects Of Meg3 Over-expression On Bc Cell Migration and Invmentioning
confidence: 99%
“…An increasing number of studies have found that lncRNAs regulate development of the central nervous system through multiple pathways . Recent studies have revealed that lncRNAs may regulate the pathogenesis of ASD at the epigenetic level . A total of 3929 differentially expressed lncRNAs have been identified in ASD patients, of which 2407 are upregulated and 1522 are downregulated, suggesting that lncRNAs may play regulatory roles in ASD .…”
Section: Introductionmentioning
confidence: 99%
“…The abnormally expanded CGG segment results in silencing of the FMR1 gene with subsequent abnormalities in the formation and function of synapses [ 141 ]. Intriguingly, several lncRNAs, including FMR4 , FMR5 , FMR6 and FMR1-AS , are transcribed from the FMR1 gene locus as well [ 142 ]. Using gene expression microarrays, Peschansky et al identified a wide array of FMR4 -responsive genes, suggesting a broad role of FMR4 [ 143 ].…”
Section: Lncrnas In Human Diseasesmentioning
confidence: 99%